Perception of the Behavior and Performance of Roller-Compacted Concrete (RCC) in the Presence of Different Types of Fly Ash and Similar Cement-Content Admixtures: A Review - Hafez M.; Farouh T.; Mozhdehi A.M.; Shariff M.S.; Muda Z.C.; Sidek L.M.; Basri H.; Almkahal Z. (Springer Science and Business Media Deutschland GmbH, 2024)
The need for massive structures such as dams, car parks, and pavements has increased in developing countries, so improving construction materials has become a trend. Since Roller-Compacted Concrete (RCC) is efficient for such projects, it is beneficial to improve it and make it affordable and environmentally friendly. In this review paper, some specific problems of RCC are studied to make the researchers aware of the qualities of RCC and the possible methods to improve RCC by using additives/substitutes like fly ash. Fly ash is inexpensive, readily available, natural, and abundant, so its use has increased in the construction industry, especially in East Asia. Fly ash reduces costs and improves project performance. It is also an environmentally friendly material. Its use as a substitute for cement and aggregates can be environmentally friendly. In this paper, a brief overview of the advantages and disadvantages of RCC is first given after introducing the nature of RCC, including its materials, manufacturing, and transportation methods. Then, the properties of RCC, such as compressive, tensile, and flexural strength, fatigue, absorption, creep, elasticity, resistance to freezing and thawing, erosion, and thermal properties, are discussed. The influence of some cement and aggregate substitutes, such as fly ash, is also described and reviewed. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.